Coastal transportation system joint taxation-subsidy emission reduction policy optimization problem. (20th February 2020) - Chen, Kang; Xin, Xu; Niu, Xiangyun; Zeng, Qingcheng
Abstract: Water transport is an important way to reduce carbon emissions in a coastal transportation system (CTS). With the goal of minimizing government financial expenditures, this paper establishes a CTS joint taxation-subsidy emission reduction policy optimization model. This model is able to optimize the government's tax and subsidy policy implementation plan for a CTS considering the non-cooperative game among shippers and the Stackelberg game led by the government and followed by carriers and shippers. Based on the active set algorithm, a local optimal solution algorithm for the model is designed. Numerical experiments are performed using the container transportation network of the Bohai Rim region of China. Two sensitivity analysis experiments are conducted on the traffic volume of the CTS and the capacity of waterway links. The results show that the government can reduce the regional carbon emission level with less investment and without significantly increasing the regional freight rate through a reasonable set of highway transportation tax and waterway transportation subsidy plans. As an important way for coastal areas to achieve green transportation, water transport will play an important role in promoting the sustainable development of coastal transport. Highlights: A solution framework is developed for governments to design subsidies and tax policy with a given carbon reduction target. An optimization model is established based on the Stackelberg game among the government, carriers and shippers. The model considers the non-cooperative game among shippers. The solution framework is applied to a real-world policy design problem. The impact of changes in maritime transport capacity and transportation demand on government spending and regional emission reductions is investigated.